2020
DOI: 10.21037/tau-20-729
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of pelvic lymph node dissection in prostate cancer

Abstract: Pelvic lymph node dissection (PLND) is an important component in the staging and prognostication of prostate cancer. We performed a narrative review to assess the literature surrounding PLND: (I) the current guideline recommendations and contemporary utilization, (II) the calculation of patient-specific risk to perform PLND using available nomograms, (III) to review the extent of dissection, and its associated outcomes and complications. Due to the improved lymph node yield, better staging, and theoretical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…A previous single‐institution series demonstrated synchronous regional lymph node metastatic disease at the time of surgery of GG2 prostate cancer in 0.6% of patients as compared to 5% in GG3 prostatectomy cases 2 . This compares with 1.3% of synchronous regional lymph node metastases identified in our study of GG2 prostatectomy specimens and 2.9% identified by Hollemans et al 26 This variability in the frequency of positive lymph nodes at radical prostatectomy may be attributed to several confounders, such as patient population, the selection of patients undergoing lymph node dissection, the extent of the lymph node dissection, the use of imaging tools and the processing of the lymph nodes for pathology examination 27 …”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…A previous single‐institution series demonstrated synchronous regional lymph node metastatic disease at the time of surgery of GG2 prostate cancer in 0.6% of patients as compared to 5% in GG3 prostatectomy cases 2 . This compares with 1.3% of synchronous regional lymph node metastases identified in our study of GG2 prostatectomy specimens and 2.9% identified by Hollemans et al 26 This variability in the frequency of positive lymph nodes at radical prostatectomy may be attributed to several confounders, such as patient population, the selection of patients undergoing lymph node dissection, the extent of the lymph node dissection, the use of imaging tools and the processing of the lymph nodes for pathology examination 27 …”
Section: Discussionsupporting
confidence: 50%
“…2 This compares with 1.3% of synchronous regional lymph node metastases identified in our study of GG2 prostatectomy specimens and 2.9% identified by Hollemans et al 26 This variability in the frequency of positive lymph nodes at radical prostatectomy may be attributed to several confounders, such as patient population, the selection of patients undergoing lymph node dissection, the extent of the lymph node dissection, the use of imaging tools and the processing of the lymph nodes for pathology examination. 27 In this study, we identified 45 cases (2.4%) with metastatic disease at the time of prostatectomy or during follow-up. This is a somewhat smaller frequency as compared to the 22 of 420 patients (5.2%) identified by Hollemans et al 26 They also reviewed their cases for the presence of adverse pathology features, including cribriform and intraductal carcinoma and tertiary grade 5.…”
Section: T a B L E 3 Association Of Adverse Growth Pattern And Site O...mentioning
confidence: 99%
“…They are extremely common, yet unlikely to be symptomatic or cause morbidity. Patients with lymphocele presented higher rates of deep venous thrombosis and pulmonary embolism [68], [70]. When it comes to severe complications the most serious ones are pulmonary insufficiency, chylous ascites (lymphatic leak) and lymphatic cysts, lymphatic fistula or chylopelvic fistula [47], [71], [72].…”
Section: Complications Of Plndmentioning
confidence: 99%
“…When it comes to severe complications the most serious ones are pulmonary insufficiency, chylous ascites (lymphatic leak) and lymphatic cysts, lymphatic fistula or chylopelvic fistula [47], [71], [72]. Thromboembolic complications are rare enough and in the majority of cases (over 99%) do not require treatment [70]. Routine pharmacological prophylaxis is currently recommended to be considered for intermediate and high thromboembolic risk indicated for ePLND.…”
Section: Complications Of Plndmentioning
confidence: 99%
See 1 more Smart Citation